MiR-143 inhibits cell proliferation and invasion by targeting DNMT3A in gastric cancer - Quan Zhang; Yong Feng; Ping Liu; Jing Yang (Tumor Biology, 2017)
Increasing evidence has suggested that MircroRNAs (miRNAs) dysregulated in pathogenesis and tumorigenicity in human cancers including gastric cancer (GC). MiR-143 had been reported to function as tumor suppressor in GC progression, however, the underlying function of miR-143 in GC still need to be well known. In the study, we revealed that miR-143 was significantly down-regulated in GC cell lines. Upregulation of miR-143 inhibited cell proliferation, invasion, S phase cell proportion and cell cycle related protein levels of Cyclin D1, CDK4 and CDK6 in GC. Furthermore, luciferase reporter assays demonstrated that DNMT3A was a direct target of miR-143 and Upregulation of miR-143 inhibited the DNMT3A mRNA and protein expression levels in GC cells. Moreover, we demonstrated that DNMT3A knockdown rescued the promoting effect of miR-143 inhibitor on cell proliferation in GC. Thus, these results demonstrated that miR-143 targeted DNMT3A in GC cells and inhibit GC tumorigenesis and progression, which may provide a novel therapeutic target of GC.